Kunst und Klassik : documenta 7 - Artisten ratlos ? - Adorno, Theodor W.; Bachmayer, H.M.; Bauer, Wolfgang; Beuys, Joseph; Dümotz, Irmtraud; Gerhardt, Titus; Golowin, Sergius; Lischka, Gerhard Johann; Müry, Andres; Oldenburg, Claes; Starck, Philippe; Warhol, Andy; et al. (Basel : Sphinx Verlag, 1982)
Beuys, Joseph ; Oldenburg, Claes ; Chia, Sandro ; Chamberlain, John ; Christian, Abraham David ; Cragg, Tony (Anthony) ; Droese, Felix ; Daniels, René ; van Elk, Ger ; Haacke, Hans ; Immendorff, Jörg ; Klossowski, Pierre ; Merz, Marisa ; Lavier, Bertrand ; LeWitt, Sol ; Merz, Gerhard ; Priapus ; Raetz, Markus ; Ruthenbeck, Reiner ; Salomé ; Shapiro, Joel ; Toroni, Niele ; Starck, Philippe ; Warhol, Andy
Documenta 7, stad Kassel. Documenta Archiv Kassel. 1982-06-18. 1982-09-28
Duits
kunstcatalogus